Intermediate recalcitrant tropical forest tree seeds: Proceedings of a workshop on improved methods for handling and storage of intermediate recalcitrant tropical forest tree seeds, 8-10 June 1995, Humlebaek, Denmark - Ouédraogo, A.S.; Poulsen, K.; Stubsgaard, F.; International Plant Genetic Resources Institute (1996)
The workshop was organized jointly with DANIDA Forest Seeds Centre, Humlebaek, Denmark. The workshop was held in recognition of the problems of handling and especially storing the seeds of many tropical tree species. The lack of cost-effective handling methods limits the planting and use of these important tree species, which in turn impacts negatively on environment and genetic resources conservation efforts. Tropical tree seeds are frequently recalcitrant or intermediate in their storage behaviour, meaning that they cannot be stored in conventional ways. These concepts are, however not well-defined, and new storage behaviours are continually being discovered. The purpose of the workshop was to gather individuals who are active in tree seed storage research, in order to: understand the present state of knowledge and formulate recommendations for future research; examine the pros and cons of alternative species for use as models in research; explore possiblities for collaboration, and bring researchers from developing and developed countries together. It is hoped that future comprehensive research efforts in this strategic field will be undertaken, based on the conclusions and recommendation of the workshop as contained in these proceedings.